Absence of Association of Tinnitus With Pre-existing Hypertension: A Population-based Study. (July 2023) - Huang, Po-Hsiu; Xirasagar, Sudha; Chen, Jin-Hua; Cheng, Yen-Fu; Kuo, Nai-Wen; Lin, Herng-Ching
Objectives: Whether tinnitus is associated with pre-existing hypertension remains uncertain. This study explored the association between tinnitus and pre-existing hypertension. Methods: We obtained data on a retrospective cohort of 542 884 cases ≥18 years old with a first-time tinnitus diagnosis from Taiwan's National Health Insurance Research Database. We used propensity-score matching to select 542 884 matched controls and performed multiple logistic regression analyses to estimate the adjusted odds of prior hypertension among patients with tinnitus versus controls. Results: Bivariate analysis showed no significant difference in the prevalence of prior hypertension between the tinnitus and no-tinnitus groups (35.58% vs 35.5%, P  = .617). Univariable logistic regression analysis confirmed the bivariate analysis finding, unadjusted odds of prior hypertension among the tinnitus group relative to controls, 1.002, 95% CI: 0.994-1.010, P  = .617). After adjusting for age, sex, monthly income, geographic location and urbanization level, hyperlipidemia, diabetes, hearing loss, obesity, anemia, rheumatoid arthritis, alcohol abuse, nicotine dependence, anxiety disorder, depressive disorder and idiopathic intracranial hypertension, the odds of prior hypertension were similar among the tinnitus and no-tinnitus groups (OR = 1.006, 95% CI: 0.997-1.016, P  = .178). Conclusions: Our population-based study found no evidence for an association between tinnitus and pre-existing hypertension.